Deciphering the efficay of multimedia based intervention for augmenting knowledge status: a clean milk production perspective - Gautam, Pawan Kumar; Mohammad, Asif (Indian Journal of Dairy Science, 2019)
A quantity of milk production has got impetus during the last decades but the quality aspect of milk is getting more and more important nowadays, as Indian population is becoming more health conscious, as well as dairy farmers of different dairy progressive states also understand the importance of clean milk production. Though the condition of West Bengal is very peculiar, as dairying in the state is still an underdeveloped proposition. The main focus of the investigation was to study the status of clean milk production vis-Ã -vis knowledge level of dairy farmers regarding clean milk production and to investigate the effectiveness of multimedia-based extension intervention on the knowledge level of farmers. The study was conducted in the Nadia and North 24 Parganas districts of West Bengal by drawing a random sample of 120 respondents covering eight villages and four blocks. Information needs analysis of the respondents was done to develop one multimedia according to their need for information. The duration of developed multimedia was 10 minutes and 11 seconds. Responses were collected before showing multimedia to assess the knowledge level of the respondents and after showing multimedia two times responses were collected. Data were collected by a structured interview schedule. After analysis of data it was found that Most of the respondents (75.00 %) preferred stripping and knuckling method of milking, because of small size of their animalâ€™s teats and also found that all the young dairy farmers (11.67 % of the respondents) fell in low knowledge score category pertaining to CMP whereas all the old farmers (10.83 % of the respondents) fell in high knowledge score category and significant difference was seen after exposing to multimedia in post test knowledge score as well as in retention knowledge test score.